Quantifying the orchard transpiration and fruit vascular flows in two high performing pear orchards grown under Mediterranean climatic conditions - Pienaar, Johan Cornelissen (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.